The Mediating Role of Raḥmah in Enhancing the Social Welfare of MSEs through a Mangrove-Based Green Economy - Hasanah Hasanah; Syaparuddin Razak; Muhammad Fakhri Amir; Kamiruddin Kamiruddin (Journal Economic Management and Business, 2026)
This study examines the mediating role of raḥmah in enhancing the social welfare of mangrove-based Micro and Small Enterprises (MSEs) in South Sulawesi, Indonesia. Integrating Islamic Mercy Theory, Sustainable Development Theory, and Social Ecology Theory, this research employs a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) on data from 240 MSE actors. The findings indicate that government policy, green economy models, and community participation significantly influence ecological awareness and the internalization of raḥmah. Furthermore, raḥmah and ecological awareness have direct positive effects on social welfare, while green economy practices and community participation exert indirect effects through raḥmah. The results highlight that social welfare is shaped not only by economic and policy factors but also by the integration of ethical values, ecological awareness, and collective engagement, contributing to a sustainable and inclusive mangrove-based development model.